2022
DOI: 10.3389/fendo.2022.1046738
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: The possible correlation between serum GRB2 levels and carotid atherosclerosis in patients with type 2 diabetes mellitus

Abstract: A Corrigendum onThe possible correlation between serum GRB2 levels and carotid atherosclerosis in patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(3) Direct Stimulation of Macrophage Inflammatory Response: TSH can reportedly activate the MAPK (ERK1/2, P38, JNK) and I kappa B/P65 pathways in macrophages. This activation results in enhanced production of inflammatory cytokines, including tumor necrosis factor (TNF)-α and Interleukin (IL)-6, thus promoting an inflammatory response within the body and encouraging monocyte recruitment ( 34 36 ). TSH also induces the generation of Reactive Oxygen Species (ROS), contributing to oxidative stress and apoptosis and ultimately facilitating the development of vulnerable plaques ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Direct Stimulation of Macrophage Inflammatory Response: TSH can reportedly activate the MAPK (ERK1/2, P38, JNK) and I kappa B/P65 pathways in macrophages. This activation results in enhanced production of inflammatory cytokines, including tumor necrosis factor (TNF)-α and Interleukin (IL)-6, thus promoting an inflammatory response within the body and encouraging monocyte recruitment ( 34 36 ). TSH also induces the generation of Reactive Oxygen Species (ROS), contributing to oxidative stress and apoptosis and ultimately facilitating the development of vulnerable plaques ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that serum TSH levels were positively correlated with cholesterol, even within the normal reference range, which also validated the influence of TSH on lipid metabolism ( 16). ( 2 (34)(35)(36). TSH also induces the generation of Reactive Oxygen Species (ROS), contributing to oxidative stress and apoptosis and ultimately facilitating the development of vulnerable plaques (16,17).…”
Section: The Pathological Mechanism Of Thr In Predicting Vulnerable C...mentioning
confidence: 99%